1974
DOI: 10.1149/1.2401958
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Vaporization Kinetics of Cr[sub 2]O[sub 3] in Oxygen from 1000° to 1300°C

Abstract: Rates of oxidative vaporization of Cr208 on preoxidized resistively heated chromium were determined in flowing oxygen at a pressure of 0.115 Torr for temperatures from 1000 ~ to 1300~ Reaction controlled rates were obtained from experimental rates by a gold calibration technique, and these rates were shown to agree with those predicted by thermochemical analysis. The activation energy obtained for the oxidative vaporization reaction corresponded numerically with the thermochemical enthalpy of the reaction. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
2

Year Published

1974
1974
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 9 publications
4
49
0
2
Order By: Relevance
“…Second, the values obtained for K v , are of the same order of magnitude as volatilization constants previously measured by other techniques directly on Cr 2 O 3 , 37 · 10 À10 g cm À2 s À1 (1,1008C) and 124 · 10 À10 g cm À2 s À1 (1,2008C) [16], and 83 · 10 À10 g cm À2 s À1 (1,1008C) and 280 · 10 À10 g cm À2 s À1 (1,2008C) [17].…”
Section: Discussionsupporting
confidence: 64%
“…Second, the values obtained for K v , are of the same order of magnitude as volatilization constants previously measured by other techniques directly on Cr 2 O 3 , 37 · 10 À10 g cm À2 s À1 (1,1008C) and 124 · 10 À10 g cm À2 s À1 (1,2008C) [16], and 83 · 10 À10 g cm À2 s À1 (1,1008C) and 280 · 10 À10 g cm À2 s À1 (1,2008C) [17].…”
Section: Discussionsupporting
confidence: 64%
“…Conventional boilers operate at maximum steam pressures of 120-150 atm (12)(13)(14)(15) in their superheaters. Supercritical boilers have superheater pressures of $240 atm (24 MPa).…”
Section: Application To Alloy Oxidation In Steammentioning
confidence: 99%
“…One suggested explanation is the doping of Cr 2 O 3 by hydrogen species deriving from the gas. 8,9 Another suggestion is that of volatile Cr-bearing species, such as CrO 3 (g), or CrO 2 (OH) 2 (g) being formed [10][11][12] at high temperature, and depleting the scale in Cr. More recently, it has been discovered that water vapor has adverse effects on chromia formers at much lower temperatures, [5][6][7]13 where the oxy-hydroxide is the predominant volatile species.…”
Section: Introductionmentioning
confidence: 99%
“…Jianian et al 8 investigated the mechanism of breakaway oxidation in Fe-Cr alloys at 1173 K in wet oxygen, and they suggested that microchannels or microcracks in the initially formed Cr 2 O 3 scale enabled [9][10][11][12][13][14][15] . Asteman et al [14][15] reported that evaporation of chromia occurred during oxidation of Type 304L at 873 K in humid oxygen.…”
Section: Introductionmentioning
confidence: 99%